Penerapan Flutter Dalam Pengembangan Aplikasi Mobile Resep Kue Indonesia - Rahmat Maulana; Richi Andrianto; Akhyar Nasution; Hanif Ahmad Hasibuan; Ari Rahmad Rahmad Siregar; Alfian Hasonangan Hasibuan (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Developed by Google, the Flutter framework has gained popularity for creating mobile apps that work across multiple platforms. In this research, we will look specifically at how Flutter can be used to make an Indonesian cake recipe application. Our goal is to assess the effectiveness and efficiency of Flutter in developing mobile apps and discover how this framework can be used to make Indonesian culinary content more accessible. The application we created allows users to easily find, view and share cake recipes from various regions in Indonesia. App testing has shown that Flutter can deliver an intuitive and responsive user interface, all with a short setup time. It has been found that Flutter offers great advantages in terms of code efficiency and maintaining consistency across platforms. The study results support the conclusion that choosing Flutter is a practical decision to develop culinary content-based mobile applications.